A study on Brand Projection of FMCG Products through Advertisements - Saha, Amitava; De, Kushal (Asian Journal of Interdisciplinary Research, 2021)
Branding aims to create an identifiable name, symbol or design, or a combination of these to distinguish the products of a producer. Brand plays a significant role in demand creation and customer retention for any product. The importance of branding is immensely felt in case of Fast Moving Consumer Goods (FMCG) products where close substitutes are readily available and imprint of the product on the customers’ minds decide the actual sale. The advertisers aim for brand association, brand distinction and brand recognition due to closeness of substitutes. In this study, 50 leading FMCG products were selected from 9 sectors and their branding strategies along with the core messages as displayed through those advertisements were assessed. It is seen that the brand name, logo and slogan are given immense importance by the advertisers. The more intense is the competition, the more aggressively the brands are emphasised through advertisements.